French cross-cultural adaptation and validity of the Moorong Self-Efficacy scale: the MSES-FR, a measure of Self-Efficacy for French people with spinal cord injury. Issue 25 (4th December 2022) - Gounelle, Marion; Cousson-Gelie, Florence; Nicolas, Benoit; Kerdraon, Jacques; Gault, Dominique; Tournebise, Hubert; Goossens, David; Leynaert, Violaine; Middleton, James; Coffy, Amandine; Gelis, Anthony
Abstract: Purpose: To adapt the Moorong Self-Efficacy Scale (MSES) in the French language and determine its psychometric proprieties. Materials and methods: After a back-translation process, an expert committee was solicited to develop the French Self Efficacy Scale, thanks to a Delphi method, regarding theoretical framework and concepts explored. A total of 201 patients with SCI were included to explore internal consistency, internal and external structure validity assessed with the General Self-Efficacy scale, MOS Health Survey Short-Form, Hospital Anxiety and Depression Scale, Way of Coping Check-list, Perceived Stress Scale, Social Support Questionnaire, Self-Esteem questionnaire, and Satisfaction With Life Scale. The retest was performed 4 days later with a randomized version of the MSES-Fr. Results: The 16 items are distributed in 3 different dimensions: Interpersonal Self-Efficacy (4 items), Instrumental Self-Efficacy (4 items) and Participation Self-Efficacy (6 items). The internal consistency was excellent (Cronbach α = .87). Results evidenced significant correlations with the MSES-Fr and other related psychological constructs (self-esteem, mood, quality of life). Reproducibility was good for the total score of the MSES-Fr (ICC = .74) and for the 3 dimensions of the scale. Conclusions: The MSES-Fr is a valid and reliable tool to assess self-efficacy in persons with spinal cord injury. Implications for rehabilitation: The Moorong Self-Efficacy Scale (MSES) is commonly used in persons with SCI for evaluating the level of perceived effectiveness in living with a disability. Validity and reliability studies of the MSES-Fr show good psychometrics properties in people with SCI. The French version of the MSES has been cross-culturally translated and is ready to be used clinically.